Körmöczi – Halfway between Radicalism and Enlightenment - TÓDOR, Csaba (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
This paper explores the relationship between theology and science in Körmöczi’s work. First, it examines the role of experimental science in Unitarian education in the late 18th and early 19th centuries. Next, it looks at how experimental sciences influenced Körmöczi’s academic work. Finally, it analyses how these scientific and philosophical thoughts affected Körmöczi’s views on faith and the consequences for his later life as a bishop. The study is divided into six sections. The first section introduces Körmöczi, connecting his study trip to Göttingen with his teaching at the Unitarian College in Kolozsvár [Cluj-Napoca]. The second contains Körmöczi’s concept of the soul, presenting his views on moral law as an internal force guiding human thought and actions. The third section analyses the impact of Kantianism on Körmöczi’s thought. The fourth section investigates Körmöczi’s threads to Schleiermacher, discussing the issue of deism and pantheism. The fifth section examines the accusation of atheism against Körmöczi, considering its context and significance within the church. And, finally, the study concludes with a summary.